AKTIVITAS TABIR SURYA EKSTRAK ETANOL DAUN Acacia auriculiformis ASAL KOLAKA MENGGUNAKAN SPEKTROFOMETRI UV-Vis - Pratama, Andri Anugrah; Ardiansyah, Akhmad; Duppa, Muhammad Taufik; Masri, Anshari (Jurnal Kesehatan Yamasi Makassar, 2025)
Excessive exposure to UV radiation can cause skin damage. Preventive measures can be taken by using sunscreen. Acacia auriculiformis is a species from the Fabaceae family, many of which are known for their antioxidant activity. Acacia auriculiformis can act as a natural sunscreen because it contains secondary metabolite compounds with conjugated double bond structures, which are known to reduce the intensity of UV exposure on the skin by absorbing ultraviolet radiation. This study aimed to identify the secondary metabolites in the ethanol extract of Acacia auriculiformis leaves from Kolaka and to determine its Sun Protection Factor (SPF) value using UV-Vis spectrophotometry. The extraction of Acacia auriculiformis leaves was carried out using the maceration method with 70% ethanol as the solvent. The sunscreen activity was determined based on the SPF values. The SPF values of the extract at concentrations of 50 ppm, 100 ppm, 150 ppm, and 200 ppm were 3.8712 (minimal protection), 6.4880 (extra protection), 9.5359 (maximum protection), and 12.5816 (maximum protection), respectively. The results indicate that sunscreen activity increases in proportion to the extract concentration. Acacia auriculiformis leaves have the potential to be developed as a sunscreen formulation.